Living experiences of patients with advanced cancer with low socioeconomic status: protocol for a systematic review of qualitative evidence. Issue 2 (1st February 2022) - An, Zifen; Meng, Xianmei; Fang, Pei; Yu, Huidan; Yu, Liping
Abstract : Introduction: The number of patients with advanced cancer is rapidly increasing, and the disease burden among those with low socioeconomic status (SES) has accordingly become a global concern. Low SES can adversely impact patients with advanced cancer. The purpose of this systematic review is to shed light on the life experiences of patients with advanced cancer with low SES to help provide targeted and effective strategies to improve their quality of life. Methods and analysis: We will include the following English databases: Cochrane Library, Cumulative Index to Nursing and Allied Health Literature, PubMed, MEDLINE, Embase, Web of Science, Joanna Briggs Institute (JBI) Database of Systematic Reviews, PsycINFO and OpenGrey, and the following Chinese databases: China National Knowledge Infrastructure, VIP Database for Chinese Technical Periodicals and Wanfang Data Knowledge Service Platform. A comprehensive search of qualitative studies on the experiences of patients with advanced cancer with low SES will be conducted from the above databases, with no age limit. Quality assessments of the studies will be independently performed by two reviewers using the JBI Critical Assessment Checklist, and any disagreements will be resolved through a discussion with a third reviewer. Relevant data will be extracted using the JBI standardised data extraction tools. The JBI meta-aggregation tool will be used to compare, analyse and summarise the original results. The reliability and credibility of the overall quality of the studies included will be evaluated using the JBI ConQual approach. Ethics and dissemination: This study is based on existing public literature and therefore does not require a formal ethics review. The results of the study may be presented in peer-reviewed international journals and presented at scientific conferences. PROSPERO registration number: CRD42021250423.